Defining Objectivity in Accounting . - Wagner, John W. (The Accounting Review, 1965)
The purpose of this article is (1) to propose a point of view for defining and applying objectivity and (2) to demonstrate the acceptability of the view and the definition when related to the needs of the profession. If researchers really wish to obtain greater objectivity in accounting, they will not do so either by eliminating the use of judgment or by permitting each individual to exercise his judgment freely. Instead, what researchers must have are (1) standards of competence and ethics, many of which they already do have, to assure that individual practitioners are capable of exercising professional judgment in an objective manner, and (2) reference points such as generally accepted objectives and principles, most of which researchers do not have in really explicit form. Even when researchers do finally develop these standards and reference points in a more adequate manner, researchers will not be eliminating the use of judgment. Instead, researchers will be making judgment more effective, more controllable, in attaining a desirable state of objectivity. It seems clear, therefore, that their task is to enhance the prestige and effectiveness of professional judgment in order to achieve greater objectivity, rather than to eliminate judgment in the mistaken notion that it is necessarily in conflict with the goal of objectivity.